2015
DOI: 10.1038/hortres.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and responses of genomic selection on key traits in apple breeding

Abstract: The application of genomic selection in fruit tree crops is expected to enhance breeding efficiency by increasing prediction accuracy, increasing selection intensity and decreasing generation interval. The objectives of this study were to assess the accuracy of prediction and selection response in commercial apple breeding programmes for key traits. The training population comprised 977 individuals derived from 20 pedigreed full-sib families. Historic phenotypic data were available on 10 traits related to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 67 publications
(57 reference statements)
13
106
3
2
Order By: Relevance
“…Correlations between estimated and observed values from the genome wide prediction model were high, showing that the model was able to estimate genotypic differences from SNP polymorphisms. However, during the cross validation, the accuracy was much lower even though similar to previous studies on apple (Kumar et al, 2012; Muranty et al, 2015) or on other species (Rutkoski et al, 2013; Fodor et al, 2014). This highlights the limit of our genome wide prediction model to predict phenotypic values for genotypes that are not included in the training set.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Correlations between estimated and observed values from the genome wide prediction model were high, showing that the model was able to estimate genotypic differences from SNP polymorphisms. However, during the cross validation, the accuracy was much lower even though similar to previous studies on apple (Kumar et al, 2012; Muranty et al, 2015) or on other species (Rutkoski et al, 2013; Fodor et al, 2014). This highlights the limit of our genome wide prediction model to predict phenotypic values for genotypes that are not included in the training set.…”
Section: Discussionsupporting
confidence: 85%
“…This highlights the limit of our genome wide prediction model to predict phenotypic values for genotypes that are not included in the training set. The prediction model accuracy is influenced by the density of the genetic map (Kumar et al, 2012; Heslot et al, 2013), the population size (Brito et al, 2011), and the heritability of traits (Combs and Bernardo, 2013; Muranty et al, 2015). Among the arguments mentioned above, the population size is probably the most limiting factor in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Muranty et al . () observed that genomic prediction accuracy is highly influenced by phenotypic distribution. The choice of model may therefore have affected the outcome of our results.…”
Section: Resultsmentioning
confidence: 99%
“…Shortcomings of this model are that censored records are considered as true survival time records and that the non-normality of survival time records violates the normality assumption of the linear mixed model. Muranty et al (2015) observed that genomic prediction accuracy is highly influenced by phenotypic distribution. The choice of model may therefore have affected the outcome of our results.…”
Section: Modelmentioning
confidence: 99%
“…Muranty et al (2015) verified that accuracy was strongly affected by phenotypic distribution. Specifically, traits that showed poor results often had skewed phenotypic distributions or low heritability.…”
Section: Introductionmentioning
confidence: 76%